Full data - Paoli, Amelie; Weladji, Robert; Holand, Øystein; Kumpula, Jouko (Dryad Digital Repository, 2019)
All the abbreviated variable names are described in detail in the paper. Variables not provided in abbreviation in the paper are not abbreviated here, but provided in full text.